Enhancement in Photocatalytic Activity of SrTiO3 by Tailoring Particle Size and Defects. Issue 18 (17th July 2019) - Kumar, Vishnu; Choudhary, Siddharth; Malik, Vidhu; Nagarajan, Rajamani; Kandasami, Asokan; Subramanian, Annapoorni
Abstract : The photocatalytic activity of polycrystalline strontium titanate (SrTiO3 ) powder having different particle sizes is investigated. The powders of SrTiO3 are ball‐milled for different time durations and characterized by x‐ray diffractometer (XRD), high‐resolution transmission electron microscopy (HRTEM), x‐ray absorption spectroscopy (XAS), UV–visible, photoluminescence (PL), and Raman spectroscopy. The crystallite size, particle size, and crystallinity of SrTiO3 decrease with an increase in ball milling time duration. While the HRTEM images show a significant reduction in the particle sizes and lattice dislocation after ball milling, the PL spectra indicate a significant enhancement of defects and vacancies in the ball‐milled SrTiO3 . The XAS measurements confirm the reduction in the valency of Ti ions due to oxygen vacancies. The photocatalytic activity of SrTiO3 is investigated using methylene blue dye under the UV‐Visible light illumination. A rapid degradation is observed for the highest time ball‐milled SrTiO3 . Small particles provide shorter path and thus decrease the probability of recombination of the photogenerated electron–hole pairs when compared with large ones. Abstract : The SrTiO3 powder is ball‐milled for 20 h. Photocatalytic activity (PCA) is performed using methylene blue dye. Pristine powder, STO‐P, and ball‐milled powder, STO‐20, decolorize the dye solution for 210 and 150 min, respectively, under UV‐Vis light illumination. The faster rate of reaction of STO‐20 is attributed to the smaller particle size and oxygen vacancies created by ball milling.